Single-Cell Biomolecular Analysis of Coral Algal Symbionts Reveals Opposing Metabolic Responses to Heat Stress and Expulsion - Petrou, Katherina; Nielsen, Daniel A.; Heraud, Philip (Frontiers in Marine Science, 2018)
The success of corals in nutrient poor environments is largely attributed to the symbiosis between the cnidarian host and its intracellular alga. Warm water anomalies have been shown to destabilize this symbiosis, yet detailed analysis of the effect of temperature and expulsion on cell-specific carbon and nutrient allocation in the symbiont is limited. Here, we exposed colonies of the hard coral Acropora millepora to heat stress and using synchrotron-based infrared microspectroscopy measured the biomolecular profiles of individual in hospite and expelled symbiont cells at an acute state of bleaching. Our results showed symbiont metabolic profiles to be remarkably distinct with heat stress and expulsion, where the two effectors elicited opposing metabolic adjustments independent of treatment or cell type. Elevated temperature resulted in biomolecular changes reflecting cellular stress, with relative increases in free amino acids and phosphorylation of molecules and a concomitant decline in protein content, suggesting protein modification and degradation. This contrasted with the metabolic profiles of expelled symbionts, which showed relative decreases in free amino acids and phosphorylated molecules, but increases in proteins and lipids, suggesting expulsion lessens the overall effect of heat stress on the metabolic signature of the algal symbionts. Interestingly, the combined effects of expulsion and thermal stress were additive, reducing the overall shifts in all biomolecules, with the notable exception of the significant accumulation of lipids and saturated fatty acids. This first use of a single-cell metabolomics approach on the coral symbiosis provides novel insight into coral bleaching and emphasizes the importance of a single-cell approach to demark the cell-to-cell variability in the physiology of coral cellular populations.